2008
DOI: 10.1161/circulationaha.107.725044
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Prevents Cerebral Ischemic Injury Through Endothelial Nitric Oxide Synthase–Dependent Mechanisms

Abstract: Background-Adiponectin is a fat-derived plasma protein that has beneficial actions on cardiovascular disorders. A low level of plasma adiponectin is associated with increased mortality after ischemic stroke; however, the causal role of adiponectin in ischemic stroke is unknown. Methods and Results-To explore the role of adiponectin in the development of acute cerebral injury, we subjected adiponectin-deficient (APN-KO) and wild-type (WT) mice to 1 hour of middle cerebral artery occlusion followed by 23 hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
136
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(145 citation statements)
references
References 38 publications
6
136
0
3
Order By: Relevance
“…Among adipokines, our biomarker panel did not include relevant molecules such as adiponectin. In agreement with our main hypothesis, linking insulin resistance with a poorer stroke outcome, both preclinical studies in rat [38] and mice [39] models of focal cerebral ischemia demonstrated a strikingly positive effect of adiponectin on cerebral flow and infarct size. Moreover, 5-year survival rate after first ever ischemic stroke was found to be higher in patients who had a lower adiponectin level determined within the first 24 hours after stroke onset [40].…”
Section: Discussionsupporting
confidence: 90%
“…Among adipokines, our biomarker panel did not include relevant molecules such as adiponectin. In agreement with our main hypothesis, linking insulin resistance with a poorer stroke outcome, both preclinical studies in rat [38] and mice [39] models of focal cerebral ischemia demonstrated a strikingly positive effect of adiponectin on cerebral flow and infarct size. Moreover, 5-year survival rate after first ever ischemic stroke was found to be higher in patients who had a lower adiponectin level determined within the first 24 hours after stroke onset [40].…”
Section: Discussionsupporting
confidence: 90%
“…The present results are consistent with other recent studies suggesting a neuroprotective role of adiponectin. Adiponectin-deficient mice exhibit enlarged brain infarction and increased neurological deficits after ischemia reperfusion compared to wild-type mice, and adenovirus-mediated supplementation of adiponectin reverses the deficit in adiponectin deficient mice and improves protection in wild-type mice (Nishimura et al 2008). Elevated plasma adiponectin attenuates cardiac ischemia/reperfusion damage in mice (Shinmura et al 2007;Gonon et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported previously that adiponectin protects neuroblastoma SH-SY5Y cells against cytotoxicity induced by 1-methyl-4-phenlyl-2,3,6-tetrahydropyridine acetaldehyde or 1-Methyl-4-phenylpyridinium ion (MPP+), and that adiponectin also exerts a cerebroprotective action attenuating cerebral ischemic injury (Jung et al 2006;Nishimura et al 2008). Excessive glutamate receptor signaling has been linked to neuronal death in epilepsy, stroke, AD, PD, and amyotrophic lateral sclerosis (Fan and Raymond 2007;O'Neill and Witkin 2007;Palop et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both adiponectin and exercise exhibit antidiabetic, antiinflammatory, antiatherogenic and cardio-protective properties (13). Recent evidence also suggests that adiponectin has neuroprotective effects in the CNS (14,15) in addition to its peripheral effects (13,16).…”
mentioning
confidence: 99%